2015
DOI: 10.1016/j.jcv.2015.06.082
|View full text |Cite|
|
Sign up to set email alerts
|

The use of next generation sequencing in the diagnosis and typing of respiratory infections

Abstract: HighlightsWe compared current viral respiratory diagnostic techniques with NGS.NGS is able to detect respiratory viruses in clinical diagnostic samples.With the current sample preparation method, NGS is less sensitive than RT-PCR.NGS provided additional sequence and typing information compared with RT-PCR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
107
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(124 citation statements)
references
References 19 publications
(19 reference statements)
14
107
0
1
Order By: Relevance
“…The literature is very limited regarding such comparisons of threshold sensitivity of qPCR and NGS. Still, a recent study showed that reverse transcription qPCR required less PCR cycle to give a upper threshold signal than NGS (Illumina MiSeq), when targeting viral DNA (23 Ct against 32 Ct in average, respectively, and corresponding to a difference of about 3 Log units) (Thorburn et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…The literature is very limited regarding such comparisons of threshold sensitivity of qPCR and NGS. Still, a recent study showed that reverse transcription qPCR required less PCR cycle to give a upper threshold signal than NGS (Illumina MiSeq), when targeting viral DNA (23 Ct against 32 Ct in average, respectively, and corresponding to a difference of about 3 Log units) (Thorburn et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…During 2002 and 2003, cell culture isolation studies and neutralization tests were used to recover cytopathic isolates and identify HAdVs. In this study, applying next generation sequencing (NGS) in pathogen identification, we sequenced the genomes of the cytopathic isolates which were originally produced in 2002 for further viral identification. The thorough investigation of throat specimens using viral culture, antisera neutralization assays, NGS, and genome‐wide phylogenetic analysis shed light on the origin and evolution of respiratory viruses, circulation of HAdV4 and non‐HAdV4 viruses and the outbreak potential by non‐HAdV pathogens in U.S. military trainees.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Using the NGS technology, the whole-genome sequencing of viruses, such as Schmallenberg virus, Dengue virus, enterovirus, and respiratory syncytial virus, has been completed. [13][14][15] This approach is cost effective and highly efficient for the recovery of viral genome sequences, taking advantage of the detection and characterization of viral genomes and viral metagenomics. 16,17 Sequence-independent, single-primer amplification (SISPA) is a methodology to synthesize and enrich viral genomes using random hexamer and SISPA sequences (5′-GCCGGAGCTCTGCAGATATC-3′).…”
Section: Introductionmentioning
confidence: 99%